Non‐Pharmacologic Multicomponent Interventions Preventing Delirium in Hospitalized People. Issue 8 (12th June 2020) - Ludolph, Paul; Stoffers‐Winterling, Jutta; Kunzler, Angela M.; Rösch, Romina; Geschke, Katharina; Vahl, Christian Friedrich; Lieb, Klaus
Abstract : BACKGROUND/OBJECTIVES: Delirium is a common neurobehavioral complication in hospitalized patients with a high prevalence in various clinical settings. Prevention of delirium is critical due to its common occurrence and associated poor outcomes. Our objective was to evaluate the efficacy of multicomponent interventions in preventing incident delirium in hospitalized patients at risk. DESIGN: Systematic review and meta‐analysis. SETTING: Hospital. PARTICIPANTS: We included a study if it was a randomized controlled trial and was evaluating effects of coordinated non‐pharmacologic multicomponent interventions in the prevention of delirium. MEASUREMENTS: We performed a systematic literature search in PubMed and CENTRAL (PROSPERO: CRD42019138981; last update May 24, 2019). We assessed the quality of included studies by using the criteria established by the Cochrane Collaboration. We extracted the measured outcomes for delirium incidence, duration of delirium, length of hospital stay, falls during hospital stay, discharge to institutional care, and inpatient mortality. RESULTS: In total, we screened 1, 027 eligible records and included eight studies with 2, 105 patients in the review. We found evidence of an effect (ie, reduction) of multicomponent interventions on the incidence of delirium (risk ratio = .53; 95% confidence interval = .41‐.69; I 2 = 0). We detected no clear evidence of an effect for delirium duration, length of hospital stay, accidental falls, and mortality. Subgroup analyses did not result in findings of substantial effect modifiers, which can be explained by the high homogeneity within studies. CONCLUSION: Our findings confirm the current guidelines that multicomponent interventions are effective in preventing delirium. Data are still lacking to reach evidence‐based conclusions concerning potential benefits for hard outcomes such as length of hospital stay, return to independent living, and mortality. J Am Geriatr Soc 68:1864‐1871, 2020.